Civic teacher strategy in the integration of nationalism and tolerance character in school based on pesantren in Yogyakarta city - Benaziria Benaziria; Mukhamad Murdiono (Journal of Social Studies (JSS), 2019)
This research aims to determine the strategy of civic education teachers in integrating nationalist character and tolerance in Junior High School based on pesantren in Yogyakarta City. Research type used in this research is qualitative research with case study method. The research subjects consisted of teachers of civic education who taught at Junior High School based on pesantren in Yogyakarta City. The research data was collected through semi-structured interview, observation and documentation. Data analysis using qualitative analysis techniques, namely data reduction, data presentation and conclusion. Data validity uses two forms of triangulation, ie source triangulation and engineering triangulation. The result of the research is that teachers have integrated nationalist character and tolerance into learning planning and implementation. Learning strategies used to integrate nationalist character and tolerance are lecture method, question and answer, and assignment. Media and learning resources used in the form of books, and video or picture display. This study finds that the implementation of civic education learning done by teachers is not based on lesson planning and effective lecture method is used as a learning strategy if teachers use media and learning resources such as video shows, slide point power usage of the media can increase the enthusiasm of learners.